The Safety and Efficacy of Mineralocorticoid Receptor Antagonists in Patients Who Require Dialysis: A Systematic Review and Meta-analysis. - Quach, K; Lvtvyn, L; Baigent, C; Bueti, J; Garg, A; Hawley, C; Haynes, R; Manns, B; Perkovic, V; Rabbat, C; Wald, R; Walsh, M (2016)
Patients who require dialysis are at high risk for cardiovascular mortality, which may be improved by mineralocorticoid receptor antagonists (MRAs).Systematic review and meta-analysis of randomized controlled trials.Adults undergoing long-term hemodialysis or peritoneal dialysis with or without heart failure.Randomized controlled trials evaluating an MRA in dialysis and reported at least one outcome of interest.Spironolactone (8 trials) or eplerenone (1 trial) compared to placebo (7 trials) or standard of care (2 trials).Cardiovascular and all-cause mortality, hyperkalemia, serum potassium level, hypotension, change in blood pressure, and gynecomastia.We identified 9 trials including 829 patients. The overall quality of evidence was low due to methodologic limitations in most of the included trials. The relative risk (RR) for cardiovascular mortality was 0.34 (95% CI, 0.15-0.75) for MRA-treated compared with control patients. The RR for all-cause mortality was 0.40 (95% CI, 0.23-0.69). The RR for hyperkalemia for MRA treatment was 3.05 (95% CI, 1.21-7.70). Sensitivity analyses demonstrated wide variability in RRs for cardiovascular mortality, all-cause mortality, and hyperkalemia, suggesting further uncertainty in the confidence of the primary results.Trial quality and size insufficient to robustly and precisely identify a treatment effect.Given the uncertainty of both the benefits and harms of MRAs in dialysis, large high-quality trials are required.